KDU University College, Utropolis, Glenmarie / Muhamad Azim Mohd Fadzer ... [et al.] - Muhamad Azim, Mohd Fadzer; Haikel Arazi Rizan, Jimmi Rizan; Nurluqman Irfan Suhaimi, Suhaimi; Nur Izzah Atira, Mohd Akbal; Nuraina Adriana Insyirah, Ishak (2019)
The building design of KDU University College, Utropolis, Glenmarie which is the main idea, is based on the planning, design, and construction strategies for Green Building. This building is certified with Green Building Index (GBI) as they have scored about 54 points in the Assessment Criteria Overall Points Score for GBI Rating. Thus, it has been certified as a green building. This report explains about organization, policy, strategy and planning of the maintenance department. This building has 13 types of building services such as Fire Fighting System, Mechanical Ventilation System, CMMS System, and etc. Every each of the building services has their own speciality for this building. At the end of this report, the surveyors have analysed that financial management in KDU University College Maintenance Department controls the expenditure regarding the income from Paramount Property.